Penerapan Differentiated Instruction dalam Meningkatkan Hasil Belajar Peserta Didik di Kelas Inklusif (Kreativasi : Journal of Community Empowerment, 2024)
This community service activity aims to implement Differentiated Instruction (DI) at SDIT Nuriz to improve inclusive classroom practices. This activity includes two-day training for teachers, six-week implementation of DI in class VI-B, and monitoring and evaluation. The results showed that 90% of teachers were more confident in implementing DI, with 85% of class activities in accordance with DI principles. The implementation of DI increased the average student test score by 14.3% and understanding of the material by 23.1%. Teacher satisfaction with the training and implementation of DI reached 88% and 85%, respectively. Future recommendations include expanding DI training and a more comprehensive evaluation of its impact on inclusive education.